Hubungan Pengetahuan Pemeliharaan Kesehatan Gigi dan Mulut dengan Keterampilan Menyikat Gigi pada Ibu PKK Tahun 2024 - ni wayan arini; I Nyoman Wirata; Ni Nyoman Dewi Supariani; Ni Luh Putu Tia Maha Lestari (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2026)
Oral health is an integral part of overall health that can affect a person's quality of life. One of the causes of neglected dental and oral health problems is a lack of knowledge about oral hygiene. Research was to determine the level of knowledge of dental and oral health maintenance and teeth brushing skills among PKK mothers in Banjar Saih, Peguyangan Kaja Village, North Denpasar District in 2024. Data collection method was by giving a questionnaire with 20 questions. Frequency of knowledge of dental and oral health maintenance PKK mothers was mostly with sufficient criteria, 24 people (52%). Frequency of tooth brushing skills was mostly with very good criteria as many as 15 people (33%). Average knowledge score was 72.93 with sufficient criteria and average tooth brushing skill score was 70.97 with good criteria. Average knowledge of dental and oral health maintenance based on education level is 81.6 with good criteria for Diploma III education. Spearman test results with a Sig value (2-tailed) of 0.001. The conclusion is that there is a relationship between the level of dental and oral health maintenance knowledge and tooth brushing skills.